Embodiment in composition : 4E theoretical considerations and empirical evidence from a case study - Pohjannoro, Ulla (SAGE, 2022)
The purpose of this study was to theorise on a composer’s corporeality from the point of view of the embodied, enacted, embedded, and extended cognition paradigm, in the light of empirical data that cover the compositional process of creating one particular piece of music. The data include related manuscripts and the composer’s verbal account of those manuscripts. Composition is seen as an interactive coping behaviour and an adaptive process of knowledge acquisition and production in a sonic environment. In this epistemic process, the composer begins working with various kinds of ideas: sounds, timbres, musical structures, experiences, philosophical thoughts. They explicate these intuitive or reflective embodied representations through different kinds of externalisations, such as musical gestures, narratives, visualisation, and finally, musical notation. This study substantiates the way in which embodied, extrabodily, embedded, and enactive processes constitute the cognitive acts of a composer, usually considered as almost purely mental. It shows how musical composition may not only be grounded but also depend on embodied knowledge that the score only partly conveys. In addition to helping composers and performers communicate in real life, the findings may be useful for identifying the different cognitive premises and circumstances that can result in discrepancies between the ways in which they interpret musical notation.
Keywords: musiikki; säveltäminen; kognitio; kognitiiviset prosessit; ruumiillisuus